ASSESSMENT OF ENVIRONMENTAL SAFETY RELATED RADIOACTIVITY EXPOSURE IN ZIRCON SAND - Diah Dwiana Lestiani; Syukria Kurniawati; Indah Kusmartini; Natalia Adventini; Woro Yatu Niken; Muhayatun Santoso (Jurnal Ecolab, 2019)
Zircon sand is one of major sources that are responsible for naturally occurring radionuclides in the earth’s crust such as 238U and 232Th. The mining and processing of zircon sand are found in several places in Indonesia such as in Bangka Belitung, Borneo and Riau. These activities are potential to produce some radioactivity exposure to the occupational area and surrounding environment. Therefore, the assessment of the environmental safety related radioactivity exposure in zircon sands is needed to ensure the safety of the worker and public. In this study, the concentration of uranium and thorium in zircon sands collected from several sites in Borneo were determined and evaluated using instrumental neutron activation analysis (INAA). Samples were irradiated in rabbit system facility of G.A Siwabessy, Serpong reactor with neutron flux ~ 1013 n.cm-2.s-1 for 15 minutes and 2 hours, and then counted with HPGe detector of gamma spectrometry. In order to assess the accuracy of the analysis, soil reference materials (RMs) were analyzed together with the samples. The results of reference material analysis showed a good agreement with the certificate value. The measurement results showed that the concentration of uranium and thorium varied widely depending on the sample origin. Uranium and thorium concentrations were 214.8 ± 101.7 and 209.9 ± 169.0 mg/kg, respectively. These values were equivalent to 2654 ± 1258 Bq/kg for 238U and 848 ± 683 Bq/kg for 232Th, respectively. The results showed the annual equivalent dose average of 2.1 ± 1.04 mSv/year and varies between 0.4 and 5.3 mSv/year.  The characterization of zircon sands using INAA showed reliable results and could be utilized to assess the level of radioactive materials content in the zircon sands related to government regulation on zircon sand radioactive exposure, as well as the precaution to reduce needless exposure of the workers and public.